An Analytical Model of Table Tennis Campus Sports Competition Trends in the Context of Sports Education Integration - Liu Hongyu; Jia Enfeng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Volunteers in sports, full-time workers in sports, trainers, coaches, and administrative support people all have varying levels of devotion to their employment and organizations. Athletes are encouraged to participate in sports by their coaches, parents, and trainers. This helps athletes maintain physical fitness and promote a healthy lifestyle in order to encourage better international and local collaboration. A sports company is made up of championships, players, a management board, local cooperation, leagues, sports clubs, and men's and women's teams that supervise and conduct the organization's activities. Protecting the rights of sport's athletes is the responsibility of sports organizations, whether temporary or permanent. The purposive sample approach and snowball sampling were used in the research design to acquire data. Purposive sampling has helped researchers to find responders who are familiar with the field of expertise, based on the appropriate degree of knowledge necessary. A questionnaire was used to obtain the information. A total of fifty people took part in this study. Out of the 50 people who responded, 35 were men and 15 were women. SEM PLS 3.3.7v was used to evaluate the collected data. The findings revealed a substantial positive relationship between the factors.